Pengaruh CR dan DER terhadap ROE pada Perusahaan Jasa Sub Sektor Konstruksi dan Bangunan - Ira Husna Rachmasari; Fatmi Handiani; Djoni Djatnika (Indonesian Journal of Economics and Management, 2021)
This research aims to determine how much the impact of CR and DER on ROE at Heavy Constructions and Civil Engineering companies for the period 2014-2019. Sample used were 8 companies using purposive sampling technique. The data used in this study is panel data so that the data will be tested using the help of Eviews 9 application and analysed using panel data regression. The selected panel data regression model is the Random Effect Model. The results of the analysis show that the CR variable partially negatively has no significant effect towards the ROE with a significance level of 0.9427 meanwhile the DER variable partially has a positive significant effect towards the ROE with a significance level of 0.0191. While simultaneous CR and DER variables affect ROE with a coefficient of determination of 15.42%